Analysis Of Effect The Price, Service, Facilities And Location To Customer Satisfaction Star Hotel In Tawangmangu - Falakh, Adhy Fajrur Nur, Sri Murwanti, S.E., MM (2016)
This research was conducted at Hotel Bintang Tawangmangu which aims to analyze the effect of price on customer satisfaction, analyzing the effect of service to customer satisfaction, analyzing the influence of facilities to customer satisfaction, analyzing the effect of the location of customer satisfaction. This study uses the survey design, the research took a sample from a population by using a questionnaire as a data collection tool. The samples used were 100 respondents Hotel Bintang Tawangmangu customers. The analytical tool used in this research is to test the instrument, the classical assumption test, data analysis (multiple linear regression analysis, t-test, F and coefficient of determination (R2)). The results of this study, there are significant positive and significant correlation between the price to customer satisfaction, there are significant positive and significant correlation between the service to customer satisfaction, there are significant positive and significant correlation between variables facilities to customer satisfaction, there are significant positive and significant correlation between variables location of customer satisfaction.